The Epidemiological Study of Caesarean Section Cases at Haji Regional General Hospital Makassar in 2024 - Fortuna, Rana Ryanti Dewi; Hinonaung, Juniarto Alexsander; Sahari, Agung; Nalanda, Refience Gratia; Al Saudi, Kurniawati Putri; Fitriani, Fitriani (Jurusan Keperawatan, Poltekkes Kemenkes Mataram, 2025)
Cesarean section (CS) is a delivery method performed when vaginal delivery poses risks to the mother and fetus. Despite its benefit under certain conditions, the increase trend of CS without clear medical indications raises concerns from both clinical and epidemiological perspectives. The rate of CS deliveries in Indonesia has increased far exceeding the WHO’s ideal threshold of 10–15%. This study aimed to describe the characteristics of mothers undergoing CS at Haji Regional General Hospital Makassar in 2024 based on maternal age, parity, delivery history, gestational age, type of CS by timing, and medical indications. This study employed a descriptive quantitative design with a retrospective approach. Data were collected from medical records of 186 mothers who underwent CS during 2024. Univariate analysis was conducted using frequency and percentage distributions. The majority of mothers, aged 20–35 years (75.8%), had parity of 2 (34.4%), and had a history of previous CS (39.2%). Most pregnancies were at term (73.1%), and most CS procedures were elective (69.9%). The most common indications were previous CS (38.7%), oligohydramnios (7.5%), failed induction (6.5%), and preeclampsia (5.9%). The findings showed that younger mothers and primiparas were more likely to undergo CS due to cephalopelvic disproportion (CPD), fetal distress, and failed induction, while multiparas with a history of CS tended to have repeat procedures. High-parity mothers were more prone to severe complications such as uterine rupture and preeclampsia. These results highlight the importance of careful pregnancy monitoring and strict evaluation of CS indications to prevent unnecessary procedures.